Synthetic Mesh Reconstruction of Chronic, Native Quadriceps Tendon Disruptions following Failed Primary Repair. (15th September 2021) - Hartline, Braden E.; Wilson, Jacob M.; Schwartz, Andrew M.; Roberson, James R.; Guild, George N.
Abstract : Case . Two patients presented with chronic knee extensor mechanism disruption after failed primary repairs. Both patients had minimal ambulatory knee function prior to surgical intervention and were treated with a synthetic mesh reconstruction of their extensor mechanism. Our technique has been modified from previously described techniques used in revision knee arthroplasty. At the one-year follow-up, both patients had improvement in their active range of motion and had returned to their previous activity. Conclusion . Synthetic mesh reconstruction of chronic extensor mechanism disruption is a viable technique that can be utilized as salvage for the persistently dysfunctional native knee.